2008
DOI: 10.1089/rej.2007.0648
|View full text |Cite
|
Sign up to set email alerts
|

Homeostatic Cytokines and Expansion of Regulatory T Cells Accompany Thymic Impairment in Children with Down Syndrome

Abstract: Down syndrome (DS), the most common chromosomal abnormality in humans, is characterized by precocious immunologic aging that results, among other things, in alterations of B and T lymphocyte subsets and natural killer cells, defective phagocytosis, and chemotaxis of polymorphonuclear leukocytes. We studied 30 children affected by DS, compared them to 29 healthy controls, and evaluated the functionality of the thymus (by measuring the amount of lymphocytes that express the signal-joint T cell receptor rearrange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
31
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 47 publications
5
31
0
2
Order By: Relevance
“…These findings suggest that AIRE activity extends beyond its previously assigned role as a regulator of TRA expression to a role consistent with regulating thymic epithelium differentiation (37). These results argue for an inborn thymic defect in central tolerance induction, rather than precocious aging of the thymus, as previously hypothesized (38)(39)(40)(41), and will be in agreement with recent studies on the function of the thymus in DS patients (17,42).…”
Section: Discussionsupporting
confidence: 90%
“…These findings suggest that AIRE activity extends beyond its previously assigned role as a regulator of TRA expression to a role consistent with regulating thymic epithelium differentiation (37). These results argue for an inborn thymic defect in central tolerance induction, rather than precocious aging of the thymus, as previously hypothesized (38)(39)(40)(41), and will be in agreement with recent studies on the function of the thymus in DS patients (17,42).…”
Section: Discussionsupporting
confidence: 90%
“…Thus, our results are in general agreement with the recent proposal by Kusters et al (6) that "the immune system in DS is intrinsically deficient from the very beginning, and not simply another victim of a generalized process of precocious aging," as hypothesized by others (7,8,54,55). Altogether, our data indicate that DS is indeed a primary, rather than a secondary, immunodeficiency, contrary to what is largely accepted (47).…”
Section: Ds: a Primary Immunodeficiency?supporting
confidence: 92%
“…Thus, the thymus in DS individuals had been reported to be smaller and hypocellular, even in infants, containing a decreased proportion of phenotypically mature TCR-ab + thymocytes (6). The number of TRECs and the size of T cell subpopulations (CD4 + , CD8 + , CD4 + CD45 + RA cells) in the peripheral blood of DS individuals have been described as reduced at various age groups (4,6,7). It was also demonstrated that DS patients present low naive T cell numbers (44).…”
Section: Impaired Thymic Function and Development In Dsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the fraction of CD8 + T cells within the T cell compartment is increased, and the fraction of CD4 + T cells decreased (9). Percentages of naive cells have been described to be decreased and memory and effector subsets to be increased in both CD4 + and CD8 + T cells (15)(16)(17). Several studies have ascribed the immunologic impairment of T cells in DS to abnormal thymus development and function (16,(18)(19)(20)(21).…”
mentioning
confidence: 99%